Fused quartz high-precision surface laser double-sided polishing method
Through multi-physical field coupled finite element simulation, laser polishing parameters are optimized, combined with experimental measurement of material characteristics, fused quartz laser double-sided polishing is achieved, solving the problem that surface shape and roughness are difficult to meet at the same time, significantly improving processing quality and reducing costs.
Patent Information
- Application Number
- CN202510071242.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-16
AI Technical Summary
The existing laser polishing methods are difficult to meet the back shape and roughness requirements of CO2 laser polishing fused quartz at the same time, and the traditional parameter cross-examination method consumes a lot of time.
Multi-physical field coupled finite element simulation is used to optimize the scanning speed and laser power during the laser polishing process of fused quartz. By experimentally measuring the specific heat capacity coefficient, viscosity coefficient and thermal conductivity coefficient of the material, a more accurate finite element model is established to realize laser double-sided polishing.
It significantly alleviates surface distortion, improves surface roughness, simplifies process flow, reduces costs, and expands the application scenarios of laser processing.
Smart Images

Figure CN119897600A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of optical element processing and manufacturing, in particular to a high-precision surface laser double-sided polishing method for fused quartz. Background Art
[0002] Fused silica glass is widely used in high-tech and modern industrial fields due to its good thermal, chemical, optical and mechanical properties. In high-power laser systems, fused silica glass is the preferred material for core components such as windows, focusing lenses, and diffraction gratings in the system due to its wide band gap. Theoretical calculations show that the intrinsic surface damage threshold of fused silica glass components can reach 100 J / cm 2 , which means that the intrinsic surface of fused quartz optical components without any processing defects can meet the development requirements of high-power laser systems. However, although the current mainstream mechanical chemical polishing method of fused quartz glass can obtain a lower surface roughness, it will produce defects such as cracks, scratches and contaminants on the processed surface, which become the source of component damage caused by laser absorption. Therefore, it is necessary to invent a method to remove surface defects and contamination and improve the surface processing quality. Laser polishing has the characteristics of no polishing auxiliary materials, non-contact processing, no introduction of surface defects and polishing hydrolysis impurities, and has a natural advantage in controlling processing defects. At present, the polished surface roughness is better than traditional polishing. However, after the components are laser polished, they will be affected by temperature fluctuations and leave ablation ripples on the surface, and residual stress will cause surface shape distortion, which greatly deteriorates the surface accuracy and limits the further development of the technology.
[0003] Patent document CN 109693039 A discloses a method for laser polishing of silicon wafer surface, which improves the roughness quality by laser polishing the surface. The disadvantage of this process scheme is that this scheme adopts a laser single-sided polishing process, which can reduce the surface roughness, but will seriously deteriorate the surface shape. At the same time, this problem is also a problem existing in most laser polishing patents, which only focus on the roughness quality after processing, and do not pay attention to the surface shape accuracy problem of a larger scale, thereby limiting the improvement of the accuracy of laser polished fused quartz components.
[0004] Patent document CN109590603A discloses a polishing method for fused quartz optical glass, which uses a temperature control feedback system and an annealing process to achieve a surface roughness of 0.18nm. The disadvantage of this solution is that the annealing process is very complicated and time-consuming. Although residual thermal stress can be eliminated, the release of thermal stress after the annealing process will seriously damage the surface shape of the component and cause surface distortion.
[0005] Patent document CN114149180A discloses a multi-physics field brittle material laser polishing method and brittle material polishing equipment. In this technical solution, ultrasonic vibration is used to assist laser polishing, thereby overcoming the easy generation of pores and cracks in the molten pool. The disadvantage of this solution is that this process mainly focuses on pores and cracks, ignoring the processing accuracy, and although ultrasonic assistance can suppress the generation of pores and cracks, it cannot eliminate the serious surface distortion caused by thermal stress introduced by laser polishing.
[0006] According to the above analysis, it is difficult for existing laser polishing methods to simultaneously meet the requirements of surface shape and roughness after CO2 laser polishing of fused quartz. In addition, it is difficult for existing polishing technologies to efficiently obtain the optimal parameters of laser polishing from these complex physical processes. CO2 laser polishing of fused quartz involves a series of complex physical processes, including the absorption of laser energy by fused quartz materials, evaporation, irradiation, material viscoelasticity, melt flow, surface tension, and Marangoni effect. Traditional parameter crossover experimental methods consume a lot of time and cost. Therefore, it is very necessary to develop a new polishing process in combination with a finite element simulation model, and take into account the complex physical processes in the laser polishing process to ensure the accuracy of surface shape and roughness. Summary of the invention
[0007] The purpose of the present invention is to propose a high-precision laser double-sided polishing method for fused quartz to solve the shortcomings of the above-mentioned background technology. The method provided by the present invention can significantly alleviate surface distortion and improve surface roughness during polishing. The method is simple to operate and low in cost, and expands the application scenarios of laser polishing.
[0008] The technical solution of the present invention is to propose a method for high-precision laser double-sided polishing of fused quartz, which mainly includes the following steps:
[0009] S1. Rinse the fused quartz element in deionized water, then ultrasonicate it in pure water at a temperature of 20-30°C for 10-15 minutes, then rinse it with deionized water, and finally blow it dry with compressed air to obtain a clean fused quartz surface;
[0010] S2. Optimize the scanning speed of the target surface, simulate the surface profile evolution and roughness of the fused quartz component after CO2 laser polishing at different scanning speeds through finite element simulation, obtain the fitting curve of scanning speed and surface roughness, and then determine the scanning speed under the minimum roughness;
[0011] S3. Place the fused quartz element on the mobile platform, set the laser polishing parameters and scanning path, adjust the polishing starting point, and process the target surface according to the scanning speed set in step S2;
[0012] S4. Optimize the polishing power of the back of the target surface, and calculate the thermodynamic temperature distribution inside the fused quartz element after CO2 laser polishing with different powers through finite element simulation, so that the temperature of the target surface and the back of the target surface exceeds the melting temperature of the material (1800K) and is lower than the evaporation temperature of the material (2500K), and then obtain the fitting curve of the element thickness and laser power;
[0013] S5. Replace the laser processing surface with the back of the target surface, measure the component thickness, select the laser power for polishing according to the fitting curve of component thickness and laser power in step S4, and keep other polishing parameters and scanning paths consistent with step S3;
[0014] S6. Ultrasonic cleaning of fused quartz components: first rinse with deionized water, then ultrasonically place in pure water at a temperature of 20-30°C for 10-15 minutes, then rinse with deionized water, and finally place on a clean bench for drying to obtain the fused quartz components after ultrasonic cleaning.
[0015] The specific steps of the finite element simulation in step S2 are:
[0016] S2.1 considers the influence of material properties changing with temperature on the polishing effect. Based on experimental measurements, the specific heat capacity coefficient, viscosity coefficient and thermal conductivity coefficient of fused quartz changing with temperature are obtained, and the three coefficients are set as the parameters of material properties in finite element simulation;
[0017] The specific heat capacity coefficient of fused quartz is expressed as:
[0018]
[0019] The viscosity coefficient of fused quartz is expressed as:
[0020]
[0021] The thermal conductivity of fused quartz is expressed as:
[0022]
[0023] S2.2 takes into account the complex physical process of laser polishing, establishes a finite element simulation model, simulates the flow field velocity distribution after laser polishing, and calculates the flow field velocity using the following formula. The flow field velocity is then integrated with the polishing time to obtain the surface morphology of the fused quartz component. The surface contour curve is then extracted and converted into independent contour points to obtain the height information of different contour points.
[0024] The flow velocity can be calculated based on the Navier-Stokes equation, taking into account the effects of surface tension and Marangoni force on the flow velocity. The formula is:
[0025]
[0026] Where η(T) is the temperature-dependent dynamic viscosity coefficient, ρ represents the density of fused quartz, u is the flow velocity, and P pre is the pressure, κ is the surface profile curvature, σ0 is the surface tension coefficient, is the temperature gradient.
[0027] The surface profile calculation formula is:
[0028]
[0029] Among them, z is the surface profile, u is the flow field velocity, and t is the polishing time;
[0030] S2.3 Calculate the roughness value of the surface morphology after polishing at different speeds according to the following formula, obtain the fitting curve of scanning speed and surface roughness, find the scanning speed corresponding to the minimum roughness, and select this scanning speed for polishing experiment;
[0031] The roughness value can be calculated using the following formula:
[0032]
[0033] Among them, RMS is the roughness, x is the profile height, and N is the number of profile points.
[0034] The fitting curve expression of scanning speed and surface roughness is:
[0035]
[0036] Among them, RMS is the roughness and v is the scanning speed.
[0037] The laser polishing parameters described in step S3 include: laser wavelength of 10.6 μm, power of 10 W-150 W, scanning speed of 1 mm / s-10 mm / s, path spacing of 20 μm-1 mm, and spot diameter of 2 mm-6 mm.
[0038] In the step S4, the thermodynamic temperature distribution is calculated using the Fourier thermodynamic equation, and the formula is:
[0039]
[0040] Where ρ represents the density of fused quartz, C p represents the specific heat capacity of fused quartz, A is the absorptivity, R is the reflectivity, P is the laser power, w0 is the laser beam radius, v s is the scanning speed, t is the polishing time, and x is the laser position;
[0041] The above formula is used to calculate the internal temperature distribution of the material under different laser powers. When the temperature is within the range of melting temperature (1800K) and evaporation temperature (2500K), the laser power corresponding to different component thicknesses is obtained. The fitting curve expressions of the two are:
[0042]
[0043] Where P is the laser power and d is the thickness of the element.
[0044] The scanning paths in steps S3 and S5 include raster scanning paths, and the starting point and the ending point of each scanning path are beyond the range of the processing surface.
[0045] The spot radius, laser power, laser frequency, laser wavelength and path spacing in the laser polishing experiment of step S3 are the same as the parameters in the finite element simulation of step S2, and the spot radius, laser power, laser frequency, laser wavelength and path spacing in the laser polishing experiment of step S5 are the same as the parameters in the finite element simulation of step S4.
[0046] In the steps S3 and S5, a thermometer is used to monitor the maximum temperature of the component surface in real time, and the laser scanning speed is feedback-controlled. If the component surface temperature is lower than the melting temperature (1800K) of fused quartz, the scanning speed is reduced; if the component surface temperature is higher than the vaporization temperature (2500K) of fused quartz, the scanning speed is increased.
[0047] Compared with the prior art, the technical effects of the present invention are as follows:
[0048] (1) Multi-physics field coupled finite element simulation is used to optimize the scanning speed and laser power during fused silica laser polishing. The method is extremely simple, avoiding a large number of parameter exploration experiments and can quickly optimize the polishing parameters;
[0049] (2) By experimentally measuring the specific heat capacity coefficient, viscosity coefficient, and thermal conductivity coefficient, the evolution law of the complex material properties with temperature was obtained, which effectively improved the accuracy of the finite element model;
[0050] (3) The present invention makes full use of the effect of laser polishing to make the material remelt and flow, significantly reducing the surface roughness; laser double-sided polishing is used to obtain a high-quality fused quartz surface. The process of the present invention is simple and low-cost, which can significantly improve the surface quality. At the same time, no chemical polishing liquid is required, which is environmentally friendly. This method expands the application scenarios of laser processing and is of great significance to the field of laser ultra-precision processing. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 The flowchart of the method for high-precision laser double-sided polishing of fused quartz surface;
[0052] Figure 2 is a schematic diagram of a laser polishing device of the present invention;
[0053] Figure 3 Schematic diagram of the laser double-sided polishing method of the present invention;
[0054] Figure 4 The figure shows the surface shape comparison of the fused quartz component before and after laser polishing, where a is the surface shape after mechanical chemical polishing, b is the surface shape after laser single-side polishing, and c is the surface shape after laser double-side polishing;
[0055] Figure 5 The roughness comparison of the fused quartz component before and after laser polishing, where a is the roughness after mechanical chemical polishing, b is the roughness after laser single-side polishing, and c is the roughness after laser double-side polishing. DETAILED DESCRIPTION
[0056] The following is a detailed description of the high-precision laser double-sided polishing method for fused quartz in conjunction with the accompanying drawings and embodiments, but this should not limit the scope of protection of the present invention.
[0057] The parameters of this embodiment are set as follows: the laser wavelength is set to 10.6μm, the laser power is set to 100W, the laser frequency is set to 95kHz, the scanning speed is 1.3mm / s, the path spacing is set to 200μm, the beam radius is set to 4mm, the scanning path is a grid path, and the starting point and the end point of each scanning path are beyond the range of the processing surface, so as to avoid the heat accumulation at the turning point. During the processing, the maximum temperature of the component surface is monitored in real time by a thermometer, and the laser scanning speed is controlled by feedback. If the surface temperature of the component is lower than the melting temperature of fused quartz (1800K), the scanning speed is reduced. If the surface temperature of the component is higher than the vaporization temperature of fused quartz (2500K), the scanning speed is increased. The workpiece to be processed is a square fused quartz plane workpiece with a side length of 30mm and a thickness of 3mm.
[0058] A method for high-precision laser double-sided polishing of fused quartz, the processing flow is as follows: Figure 1 As shown in the figure, the method includes the following steps:
[0059] 1) Rinse the fused quartz element in deionized water, then ultrasonicate it in pure water at a temperature of 20-30°C for 10-15 minutes, then rinse it with deionized water, and blow it dry with compressed air to obtain a clean fused quartz surface;
[0060] 2) Optimize the scanning speed of the target surface, perform finite element simulation using COMSOL software, simulate the surface profile evolution and roughness of the fused quartz component after CO2 laser polishing at different scanning speeds, obtain the fitting curve of scanning speed and surface roughness, and then determine the scanning speed under the minimum roughness; the specific steps are:
[0061] ① The influence of material properties changing with temperature on the polishing effect was considered. The specific heat capacity coefficient, viscosity coefficient and thermal conductivity coefficient of fused quartz changing with temperature were obtained according to experimental measurements. The three coefficients were set as parameters of material properties in finite element simulation, and the other parameters were consistent with the experimental parameters.
[0062] The specific heat capacity coefficient of fused quartz is expressed as:
[0063]
[0064] The viscosity coefficient of fused quartz is expressed as:
[0065]
[0066] The thermal conductivity of fused quartz is expressed as:
[0067]
[0068] ② Establish a simulation model and divide it into grids with a minimum grid size of 2nm. Then set the material characteristic parameters according to the material characteristics in ①, and then set the polishing parameters the same as the experiment, substitute them into the model settings for transient simulation calculations, run the software to calculate the flow field velocity, and then integrate the flow field velocity with the polishing time to obtain the surface morphology of the fused quartz component, and then extract the surface contour curve, transform the surface contour curve into independent contour points, and obtain the height information of different contour points.
[0069] The flow field velocity can be calculated based on the Navier-Stokes equation, taking into account the effects of surface tension and Marangoni force on the flow field velocity. The governing equation of surface tension is:
[0070]
[0071] Where κ is the surface profile curvature and σ0 is the surface tension coefficient.
[0072] The governing equation for the Marangoni force is:
[0073]
[0074] is the temperature gradient.
[0075] The flow rate calculation formula is:
[0076]
[0077] Where η(T) is the temperature-dependent dynamic viscosity coefficient, ρ represents the density of fused quartz, u is the flow velocity, and P pre is the pressure, κ is the surface profile curvature, σ0 is the surface tension coefficient, is the temperature gradient.
[0078] The surface profile calculation formula is:
[0079]
[0080] Among them, z is the surface profile, u is the flow field velocity, and t is the polishing time.
[0081] ③ Calculate the roughness value of the surface morphology after polishing at different speeds according to the following formula, obtain the fitting curve of scanning speed and surface roughness, find the scanning speed corresponding to the minimum roughness, and select this scanning speed for polishing experiment.
[0082] The roughness value can be calculated using the following formula:
[0083]
[0084] Among them, RMS is the roughness, x is the profile height, and N is the number of profile points.
[0085] The fitting curve expression of scanning speed and surface roughness is:
[0086]
[0087] Among them, RMS is the roughness and v is the scanning speed.
[0088] 3) Place the fused quartz element on the mobile platform, set the laser polishing parameters and scanning path, and adjust the polishing starting point position. Process the target surface according to the scanning speed set in step 2). The schematic diagram of the laser polishing device is shown in Figure 2 As shown;
[0089] 4) The polishing power of the back side of the target surface is optimized, and the thermodynamic temperature distribution inside the fused quartz element after CO2 laser polishing with different powers is calculated by finite element simulation. The thermodynamic temperature distribution is calculated using the Fourier thermodynamic equation, and the formula is:
[0090]
[0091] Where ρ represents the density of fused quartz, C p represents the specific heat capacity of fused quartz, Q represents the laser heat source;
[0092] The expression of laser heat source is:
[0093]
[0094] Where A is the absorptivity, R is the reflectivity, P is the laser power, w0 is the laser beam radius, v s is the scanning speed, t is the polishing time, and x is the laser position.
[0095] The above formula is used to calculate the internal temperature distribution of the material under different laser powers. When the temperature is within the range of melting temperature (1800K) and evaporation temperature (2500K), the laser power corresponding to different component thicknesses can be obtained. The fitting curve expressions of the two are:
[0096]
[0097] Where P is the laser power and d is the thickness of the element.
[0098] It is worth noting that the parameters in the laser polishing experiment are the same as those in the finite element simulation.
[0099] 5) Replace the laser processing surface with the back of the target surface, measure the component thickness, and select the laser power for polishing according to the fitting curve of component thickness and laser power in step 4). Other polishing parameters and scanning paths are consistent with step 3). The schematic diagram of laser double-sided polishing is as follows: Figure 3 As shown;
[0100] 6) Ultrasonic cleaning of fused quartz components: first rinse with deionized water, then ultrasonically place in pure water at a temperature of 20-30°C for 10-15 minutes, then rinse with deionized water, and finally place on a clean bench for drying to obtain the fused quartz components after ultrasonic cleaning.
[0101] The surface shape of the fused quartz element processed by the method of the present invention is detected by laser interferometer (VeriFire XPZ, Zygo). The results are as follows: Figure 4 As shown, a is the shape after mechanical chemical polishing, b is the shape after laser single-side polishing, and c is the shape after laser double-side polishing. The roughness of the fused quartz element processed by the method of the present invention is detected by a 4D optical profiler (NanoCam Sq, 4D Technology), and the test size is 0.5mm×0.5mm. The results are as follows: Figure 5 As shown, a is the roughness after mechanical chemical polishing, b is the roughness after laser single-side polishing, and c is the roughness after laser double-side polishing. The results show that compared with the laser single-side polishing method, the surface shape PV and RMS of the fused quartz component processed by the method of the present invention are reduced from 2.140λ and 0.435λ to 0.957λ and 0.194λ respectively. After being processed by the method of the present invention, the RMS value of the roughness of the fused quartz component is reduced from 1.349nm of the initial surface to 0.270nm. When the processing method of the present invention processes the fused quartz component, the surface shape deterioration can be greatly suppressed and the surface roughness can be significantly improved. The processing results observed in the embodiment prove that the invention has a very significant practical effect.
[0102] The scanning speed and laser power in the fused quartz laser polishing process are optimized by multi-physics field coupling finite element simulation. The method is extremely simple and avoids a large number of parameter exploration experiments, and the polishing parameters can be quickly optimized. In addition, the evolution law of the complex characteristics of the material with temperature is obtained by experimentally measuring the specific heat capacity coefficient, viscosity coefficient and thermal conductivity coefficient, which effectively improves the accuracy of the finite element model. The high-quality fused quartz surface is obtained by laser double-sided polishing. The process of the present invention is simple and low-cost, which can significantly improve the surface quality and reduce the roughness. At the same time, no chemical polishing liquid is needed, which is environmentally friendly. This method expands the application scenarios of laser processing and is of great significance to the field of laser ultra-precision processing.
Claims
1. A method for high-precision laser double-sided polishing of fused quartz, characterized in that: The main steps include: S1 fused quartz surface pretreatment: rinse the fused quartz component in deionized water, then ultrasonicate it in pure water at a temperature of 20-30°C for 10-15 minutes, then rinse it with deionized water, and finally blow it dry with compressed air to obtain a clean fused quartz surface; S2 target surface scanning speed optimization: simulating the CO2 laser polishing results at different scanning speeds through finite element simulation, and then determining the scanning speed at the minimum roughness; S3 target surface processing: place the fused quartz component on the mobile platform, set the laser polishing parameters and scanning path, and adjust the polishing starting point position, and process the target surface according to the scanning speed set in step S2; S4 Optimization of polishing power on the back of the target surface: The thermodynamic temperature distribution inside the fused quartz component after CO2 laser polishing with different powers is calculated by finite element simulation, so that the temperature of the target surface and the back of the target surface exceeds the melting temperature of the material (1800K) and is lower than the evaporation temperature of the material (2500K), and then the fitting curve of the component thickness and laser power is obtained; S5 target surface back side processing: replace the laser processing surface with the back side of the target surface, measure the component thickness, select the laser power for polishing according to the fitting curve of component thickness and laser power in step S4, and keep other polishing parameters and scanning paths consistent with step S3; Ultrasonic cleaning of S6 fused quartz components: first rinse with deionized water, then ultrasonically place in pure water at a temperature of 20-30°C for 10-15 minutes, then rinse with deionized water, and finally place on a clean bench for drying to obtain the fused quartz components after ultrasonic cleaning.
2. The method for high-precision laser double-sided polishing of fused quartz according to claim 1, characterized in that: The specific steps of the finite element simulation in step S2 are: S2.1 According to experimental measurements, the specific heat capacity coefficient, viscosity coefficient and thermal conductivity coefficient of fused quartz that vary with temperature are obtained, and the three coefficients are set as parameters of material properties in finite element simulation; The specific heat capacity coefficient of fused quartz is expressed as: The viscosity coefficient of fused quartz is expressed as: The thermal conductivity of fused quartz is expressed as: S2.2 Establish a finite element simulation model to simulate the flow field velocity distribution after laser polishing, and calculate the flow field velocity by the following formula. Integrate the flow field velocity with the polishing time to obtain the surface morphology of the fused quartz component, and then extract the surface contour curve, transform the surface contour curve into independent contour points, and obtain the height information of different contour points; The flow field velocity is calculated based on the Navier-Stokes equation, taking into account the effects of surface tension and Marangoni force on the flow velocity. The formula is: Where η(T) is the temperature-dependent dynamic viscosity coefficient, ρ represents the density of fused quartz, u is the flow velocity, and P pre is the pressure, κ is the surface profile curvature, σ0 is the surface tension coefficient, is the temperature gradient. The surface profile calculation formula is: Among them, z is the surface profile, u is the flow field velocity, and t is the polishing time; S2.3 Calculate the roughness value of the surface morphology after polishing at different speeds according to the following formula, obtain the fitting curve of scanning speed and surface roughness, find the scanning speed corresponding to the minimum roughness, and select this scanning speed for polishing experiment; The roughness numerical calculation formula is as follows: Among them, RMS is the roughness, x is the profile height, and N is the number of profile points. The fitting curve expression of scanning speed and surface roughness is: Among them, RMS is the roughness and v is the scanning speed.
3. The method for high-precision laser double-sided polishing of fused quartz according to claim 1, characterized in that: The laser polishing parameters described in step S3 include: laser wavelength of 10.6 μm, power of 10 W-150 W, scanning speed of 1 mm / s-10 mm / s, path spacing of 20 μm-1 mm, and spot diameter of 2 mm-6 mm.
4. The method for high-precision laser double-sided polishing of fused quartz according to claim 1, characterized in that: The scanning paths in steps S3 and S5 include raster scanning paths, and the starting point and the ending point of each scanning path are beyond the range of the processing surface.
5. The method for high-precision laser double-sided polishing of fused quartz according to claim 1, characterized in that: In step S4, the thermodynamic temperature distribution is calculated using the Fourier thermodynamic equation, and the formula is: Where ρ represents the density of fused quartz, C p represents the specific heat capacity of fused quartz, A is the absorptivity, R is the reflectivity, P is the laser power, w0 is the laser beam radius, v s is the scanning speed, t is the polishing time, and x is the laser position; The above formula is used to calculate the internal temperature distribution of the material under different laser powers. When the temperature is within the range of melting temperature (1800K) and evaporation temperature (2500K), the laser power corresponding to different component thicknesses is obtained. The fitting curve expressions of the two are: Where P is the laser power and d is the thickness of the element.
6. The method for high-precision laser double-sided polishing of fused quartz according to claim 1, characterized in that: The spot radius, laser power, laser frequency, laser wavelength and path spacing in the laser polishing experiment of step S3 are the same as the parameters in the finite element simulation of step S2, and the spot radius, laser power, laser frequency, laser wavelength and path spacing in the laser polishing experiment of step S5 are the same as the parameters in the finite element simulation of step S4.
7. The method for high-precision laser double-sided polishing of fused quartz according to claim 1, characterized in that: In the steps S3 and S5, a thermometer is used to monitor the maximum temperature of the component surface in real time, and the laser scanning speed is feedback-controlled. If the component surface temperature is lower than the melting temperature (1800K) of fused quartz, the scanning speed is reduced; if the component surface temperature is higher than the vaporization temperature (2500K) of fused quartz, the scanning speed is increased.
Citation Information
Patent Citations
Method for laser polishing of surface of silicon wafer
CN109693039A
Processing method for improving damage threshold of fused quartz element
CN114149180A
Method for preparing microfluidic device through picosecond laser-induced quartz glass internal cracks
CN109551123A
Laser beam polishing method of fused quartz optical glass
CN109590603A
Two-step polishing method for large-diameter fused quartz element based on CO2 laser
CN115365660A
Cited By
Full-automatic 3D double-sided laser flash removing equipment and method and medium
CN120839294A
Method for repairing atomic-scale defect by CO2 laser based on densification effect
CN122077203A
A CO2 laser repair method for atomic-level defects based on densification effect
CN122077203B